2021
DOI: 10.1371/journal.pntd.0009611
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of chromoblastomycosis

Abstract: Background Chromoblastomycosis (CBM), represents one of the primary implantation mycoses caused by melanized fungi widely found in nature. It is characterized as a Neglected Tropical Disease (NTD) and mainly affects populations living in poverty with significant morbidity, including stigma and discrimination. Methods and findings In order to estimate the global burden of CBM, we retrospectively reviewed the published literature from 1914 to 2020. Over the 106-year period, a total of 7,740 patients with CBM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 126 publications
5
67
0
Order By: Relevance
“… 24 , 25 Strategies with other azoles, other than itraconazole or posaconazole, have also been used. 26 The use of voriconazole in cats has been proposed as a first-line treatment. 2 However, the clinical recurrence when stopping treatment, as well as the cost of the medication, does not favor its use as the drug of choice.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 Strategies with other azoles, other than itraconazole or posaconazole, have also been used. 26 The use of voriconazole in cats has been proposed as a first-line treatment. 2 However, the clinical recurrence when stopping treatment, as well as the cost of the medication, does not favor its use as the drug of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Chromoblastomycosis is a neglected and chronic infectious disease that has a peculiar characteristic, the transepidermal elimination of fungal structures in its early stages. Considered one of the implantation mycoses, the disease is present in several countries especially in developing countries; chromoblastomycosis is relatively common in Brazil [ 2 ]. The etiological agents are geophilic melanized fungi present in nature, particularly in rural areas.…”
Section: Case Discussionmentioning
confidence: 99%
“…The tropical oceans produce about 80 tropical storms per year, of which about two-thirds are severe (classi ed on a Sa r-Simpson intensity scale of 1 or higher). Almost 90% of storms form within 20° north or south of the equator (Britannica, 2022;National Hurricane Center and Central Paci c Hurricane Center National Oceanic and Atmospheric Administration, 2022), and CBM is also endemic in this region (Queiroz-Telles et al, 2017;Santos et al, 2021). Notably, the ndings of DeLeon-Rodriguez et al, (2013) (DeLeon-Rodriguez et al, 2013 suggested that fogging of large fungal spore communities occurs during tropical hurricanes, and airborne fungi may remain viable after being carried aloft (Alsante et al, 2021;Mayer et al, 2020), where long-distance, transcontinental and even oceanic transport occurs.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of endemic tropical diseases caused by prevalent fungi (Boekhout et al, 2021), bacteria, viruses, and parasites are expanding their geographical distribution (Tedersoo et al, 2021), while a large number of natural products of tropical biomes have excellent therapeutic e cacy and show promise for treating these diseases (Adegboye et al, 2021). This provides new possible treatment options for the large number of patients with severe illnesses (Khan et al, 2019) or very poor treatment results (Schwalb & Seas, 2020) who are currently widespread, because the complete cure of severe cases of Fonsecaea spp.-caused infections is a great challenge for clinicians and researchers (Santos et al, 2021). At present, the exact cost of CBM driven by etiological Fonsecaea agents is unknown, as there is no national surveillance mechanism in China to examine CBM in sentinel centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation